Strategi Belajar Mawapres Fis dalam Meningkatkan Hasil Belajar - Vynna Fermanayudha; Martini Martini; Achmad Nur Hidayaht (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
This study aims to obtain data on individualized learning strategies used by FIS UNJ students in improving their GPA. To get a clear picture of the individualized learning strategies of fis unj students, researchers use descriptive methods with a qualitative approach by making in-depth observations so as to produce valid data according to the case studies discussed. Data collection techniques were carried out by structured interviews and observations. The results concluded that fis unj students with achievements in non-academic fields utilize individual learning strategies such as awareness of responsibility and the ability to manage time efficiently in achieving satisfactory academic goals and apply appropriate individual learning styles that contribute to improving learning performance to achieve the cumulative grade point average results they expect.